THE POLITICS AND ECONOMY OF ELECTION VIOLENCE IN NIGERIA’S FOURTH REPUBLIC - Unya, Ikenna Ukpabi; Asemota, Roberts Osatohanmwen (EBSU Journal of Social Sciences and Humanities, 2025)
Although election violence in Nigeria dates back to pre-independence era, it has become more frequent and deadly since the Fourth Republic that began in 1999. With over 626 deaths in election-related violence in 2019, observer groups believe that the 2019 general election remains one of the most violent in Nigeria’s electoral democracy. This paper examines the factors that underpin and sustain election violence in Nigeria, especially in the Fourth Republic. The argument here is that election violence in Nigeria is rooted in two mutually reinforcing politico-economic factors; the structure of the Nigerian state and its governance system, on the one hand, and the character and worldview of its ruling class elite, on the other. Findings indicate that election violence not only threatens the stability of electoral process, but it also undermines the legitimacy of electoral outcomes and political regimes. Thus, a radical alteration of the composition of the political class elite through a repudiation of the age long process of political leadership may be one way of address the challenges of election violence in Nigeria.